Quercus ilex root growth in response to heterogeneous conditions of soil bulk density and soil NH4-N content - Cubera, Elena; Moreno, Gerardo; Solla, Alejandro (Soil and Tillage Research, 2009)
A greenhouse study examined the effects of heterogeneous conditions of soil bulk density and soil NH4-N content on the growth of holm oak (Quercus ilex L.) seedlings over an 8-month period. Heterogeneity of soil was produced inside 150 cm depth pots, by applying manual compaction or enriching different soil layers with NH4 (vertical heterogeneity) and, by splitting the root system into two columns with differing soil bulk density or NH4 conditions (horizontal heterogeneity). Root distribution patterns were assessed by collecting roots within layers, each 10 cm depth, and by recording both the ﬁne (diameter <2 mm) and the coarse (diameter 2 mm) root biomass. Root systems signiﬁcantly responded to the vertical gradients of soil bulk density, decreasing their maximum depth and showing lower values of ﬁne root densities at the layers with a dry bulk density of 1.62 Mg m3 . The split-root system showed that maximum rooting depth of the axis with a dry bulk density of 1.38 Mg m3 was limited by the reduced rooting depth of the adjacent more compacted axis. Root systems were less dense in the NH4 soil treatment than in the control soil treatment (34 mg dm3 vs. 212 mg dm3 ), even at the lowest rate used (0:1 g NH4 L 1 soil ). This high sensitivity to NH4 conducted to a signiﬁcant decrease of shoot height and root depth (50 and 43%, respectively). The split-root system showed that unfavourable conditions of NH4 content have local consequences on the rooting depth and systemic consequences on the ﬁne root density. The implications of root growth restrictions for Q. ilex natural regeneration, seedling survival, and decline are discussed.
Keywords: Oak decline; Quercus ilex; Root density; Root depth; Soil bulk density; Soil NH4 content